Contemporary organisational pathologies in police information sharing: new contributions to Sheptycki's lexicon of intelligence in policing - Stanier, Ian Phillip (2013)
Inadequate information sharing practices remain a significant contributory factor in police intelligence and investigative failure. The consequences are serious, as ineffective and inefficient policing present direct threats to the very community police seek to protect. The modern digital environment, enabling legislation, high level commitments to information sharing, and, depressingly, recurring criticism arising out of high profile information management failures, appear not to have made any discernible positive difference. This thesis seeks to understand why information sharing failures still stubbornly remain, using as its starting point Sheptycki's (Sheptycki, 2004) eleven organisational pathologies in information sharing in police intelligence systems. This thesis's research reveals a complex inter-connected array of factors actively undermining effective information sharing within policing and wider law enforcement but holds that three are central to any attempt to improve processes. It contends that a combination of codified and simplified legislation and regulation, a professionalization of the role of the intelligence operative and the criticality and smarter use of available data management technologies, can significantly reduce information sharing pathologies. Accordingly, the thesis offers suggestions for essential next steps to tackle these three key challenges to enhanced police information sharing.